PERBANDINGAN KINERJA SAHAM PERUSAHAAN TERAFILIASI ISRAEL DAN NON-ISRAEL DI BEI DALAM KONDISI ISU GEOPOLITIK TAHUN 2023 - Ishmah Karimatul Fathi; Vina Anggilia Puspita (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
Geopolitical instability can having a significant impact on stock markets, including in Indonesia. The researcher’s study aims to finding about differences in stock performance between Israel-affiliated companies and non-Israel companies listed on the Indonesia Stock Exchange (IDX) in the context of geopolitical issues. The research method used is a quantitative approach with a comparative analysis using the Independent Sample T-Test. Yahoo Finance provided secondary data on the daily stock returns of selected companies. The outcome indicate that there is a significant difference between stock returns between Israel-affiliated and non-Israel companies, with a significance value of 0.020 (< 0.05). These findings suggest that investors in the IDX respond differently to geopolitical issues based on company affiliation. Geopolitical factors can be an essential element in investment decision-making in the Indonesian stockmarket. Keywords: Stock performance; geopolitical issues; Israeli-affiliated companies; Indonesia Stock Exchange.